A review of the role of digitalization in health risk management in extractive industries – a study motivated by COVID-19. Issue 2 (4th August 2021) - Nguyen, Trung; Gosine, Ray; Warrian, Peter
Abstract : Purpose: While disruptions as a result of the COVID-19 pandemic resulted in the failure of some companies, others embraced innovative digital technologies to face the challenge posed by COVID-19. The COVID-19 crisis is also an opportunity for the extractive industry (EI) sectors to review their digitalization processes. The purpose of this paper is to conduct a systematic review of infectious disease mitigation in EI and to evaluate the resilience of these industries as they address pandemic prevention and control. Design/methodology/approach: Multi-case studies including digital and organizational responses to COVID-19 were analyzed to evaluate the readiness of health risk management (HRM) and resilience of EIs against the pandemic. The evaluation uses Google Scholar and Trends searches to compare the level of relevant activity in EIs with other industries. Findings: Although EI sectors have various plans for minimizing pandemic impacts, unexpected disruptions and delays of the COVID-19 responses revealed many limitations of the existing HRM system. Digital technologies (e.g. artificial intelligence-based public health monitoring, digital collaboration, wearable health tracking and 3D printing) demonstrated their remarkable benefits in the pandemic responses and nontechnical elements affecting technology adoption (TA). Originality/value: Lessons learned from the deployment of digital technologies against the pandemic help to improve the organizational capacity to deal effectively with future outbreaks and suggest lessons for the future trajectory of TA in these industries.